THE CURRENT STATE OF POLYMER WASTE MANAGEMENT - YEFREMOVA, Olha; IVANISHENA, Tetiana; ISHCHUK, Tetiana; TRUKHINA, Oksana; YEFREMOVA, Yuliia (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In the work presents the results of the analysis of the current state of polymer waste management in Ukraine and the world. It is known that the vast majority of such waste accumulates in landfills or enters the natural environment. Such a threatening situation requires the search for an effective solution to the problem of polymer waste management, since its processing contributes to the preservation of natural resources and the solution to the problem of the shortage of polymer raw materials. The quantitative and qualitative composition of such waste was analyzed and it was established that the most frequently used types of plastic are polyolefins. Since the management of a large amount of plastic waste is a difficult task, the state regulation of the polymer waste management system is of great importance in this area. In Ukraine, this is being implemented thanks to the adoption of the National Waste Management Strategy in 2017. An assessment of possible ways of recycling polymer waste was carried out in order to solve the problem of shortage of polymer raw materials. Today, polymer waste can be disposed of in three directions: material (polymer-raw material); raw materials and energy.  The main methods of their processing and directions of use of the obtained products were studied. The most popular methods are physical, chemical and thermal. It has been established that the recyclates obtained in this way can most often be used in the food, processing, construction industries, as well as in automobile and aircraft construction. A fairly promising direction of using recycled products is light industry products with additional hydrophobic, fire-resistant, flame-retardant, conductive, heat-insulating, anti-corrosion, airtight and other operational properties.
Keywords: polymer waste management; polymer waste; methods of waste processing